.


:




:

































 

 

 

 


.




.

y = f (x) 0. 0 D D f (x 0)= f (x 0+D ) f (x 0).

y = f (x) 0 D f (x 0) D , D . .

, : = .

=¥, , f 0 .

f 0 :

1. 0 D D f (x 0)= f (x 0+D ) f (x 0).

2. .

3. . , f 0, = .

y = f (x) ( ). , f 0 () , () :

.

0 , , .

, 0, . 0, .

D 1 , f . Î D 1 , D 1. y = f (x) , .

.

: k , f 0, =tg a, a (.4.1).

f 0 , f 0.

г , f 0: .

: , , ; , , , .

: t, , .

 





:


: 2015-05-07; !; : 784 |


:

:

, - , ; , - .
==> ...

1949 - | 1933 -


© 2015-2024 lektsii.org - -

: 0.008 .